A STUDY OF CLINICAL FEATURES AND LABORATORY PROFILE OF DENGUE FEVER IN OUTPATIENT SETTING - Goweda, Reda; Faisal, Ahmed (Malaysian Journal of Public Health Medicine, 2020)
Dengue fever (DF) is one of the common mosquito-borne viral diseases. It is transmitted by Aedes aegypti and Aedes albopictus.The aim to study the clinical and laboratory manifestations of serologically confirmed cases of DF in outpatient clinics.This cross-sectional study was carried out in outpatient setting. According to WHO criteria all patients above 14 years old who were suspected to have DF were tested by IgM dengue antibody test. Additionally all patients underwent history, clinical examination and investigation including complete blood count, liver function test and abdominal ultrasound. Data was analyzed using SPSS version 20.Out of 126 patients presented with acute febrile illness, 71 (56.3%) had seroreactivity for dengue IgM antibodies. Fever, headache and muscloskeletal pain were the most common clinical presentation (100%). Decreased appetite (92.9%) , retro-orbital pain (78.8%) and dizziness(64.7%) were the next common symptoms. 29(40.8%) had hepatomegally, 11 (15.4%) had splenomegally.Elevated serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were observed in 58(81.6%) and 53(74.6%) respectively. Lastly; Fever associated with headache, retro-orbital pain, along with thrombocytopenia and elevated liver transaminases should prompt a clinician on the possibility of DF. Increased community awareness and vector control measures need to be strengthened to reduce the burden of dengue cases.